Stasimon Contributes to the Loss of Sensory Synapses and Motor Neuron Death in a Mouse Model of Spinal Muscular Atrophy - Christian M. Simon; Meaghan Van Alstyne; Francesco Lotti; Elena Bianchetti; Sarah Tisdale; D. Martin Watterson; George Z. Mentis; Livio Pellizzoni (Cell Reports, 2019)
Summary: Reduced expression of the survival motor neuron (SMN) protein causes the neurodegenerative disease spinal muscular atrophy (SMA). Here, we show that adeno-associated virus serotype 9 (AAV9)-mediated delivery of Stasimon—a gene encoding an endoplasmic reticulum (ER)-resident transmembrane protein regulated by SMN—improves motor function in a mouse model of SMA through multiple mechanisms. In proprioceptive neurons, Stasimon overexpression prevents the loss of afferent synapses on motor neurons and enhances sensory-motor neurotransmission. In motor neurons, Stasimon suppresses neurodegeneration by reducing phosphorylation of the tumor suppressor p53. Moreover, Stasimon deficiency converges on SMA-related mechanisms of p53 upregulation to induce phosphorylation of p53 through activation of p38 mitogen-activated protein kinase (MAPK), and pharmacological inhibition of this kinase prevents motor neuron death in SMA mice. These findings identify Stasimon dysfunction induced by SMN deficiency as an upstream driver of distinct cellular cascades that lead to synaptic loss and motor neuron degeneration, revealing a dual contribution of Stasimon to motor circuit pathology in SMA. : SMN deficiency causes motor circuit dysfunction in SMA. Simon et al. show that Stasimon—an ER-resident protein regulated by SMN—contributes to sensory synaptic loss and motor neuron death in SMA mice through distinct mechanisms. In motor neurons, Stasimon dysfunction induces p38 MAPK-mediated phosphorylation of p53 whose inhibition prevents neurodegeneration. Keywords: spinal muscular atrophy, SMN, Stasimon, Tmem41b, p53, p38 MAPK, neurodegeneration, motor neurons, proprioceptive neurons